Australian social attitudes IV : Australia in the age of insecurity - Wilson, Shaun; Hadler, Markus (Public and social policy., 2018)
In the decade following the end of the Howard administration, Australian politics has been defined by growing uncertainty and the emergence of popular disaffection with the political class, similar to that found in the United States and Britain. Australian Social Attitudes IV: Australia in the Age of Insecurity is an in-depth look at the economic and geopolitical tensions that pervade Australian discourse.